Climate shock response and resilience of smallholder farmers in the drylands of south-eastern Zimbabwe - Nkonya, Ephraim M.; Kato, Edward; Msimanga, Mthabisi; Nyathi, Nomqhele (Frontiers Media, 2023)
Climatic shocks are exerting pressure on livelihoods of Zimbabwe's smallholder farmer—who irrigate only 2% of their farms. The smallholder farmers in drought-prone areas are more exposed to drought because of their limited ability to cope with shocks and their greater concentration in less favorable climatic regions. This study was done to analyze shock-response approaches, which farmers use to cope with climatic shocks. Both quantitative and qualitative approaches were used to analyze impact of World Vision Zimbabwe (WVZ) and other actors' interventions on farmer resilience to climatic shocks. Results show that mixed cropping and diversification in general were among the major strategies that pastoralists and crop farmers used to cope with climatic shocks. Crop farmers diversified types of crops as well as raising livestock. Similarly, pastoralists started growing short-term crops. Other coping strategies included intercropping, selling livestock, moving livestock to other places that did not experience drought. Both crop producers and livestock keepers engaged in nonfarm activities. About 60% of WVZ households reported that World Vision and partners helped them respond to shock and build resilience against climate change. These coping strategies had favorable impacts on household welfare. Diversification increased dietary diversity index by more than two and the increase was much greater among female-headed households than male-headed households. The WVZ intervention also significantly reduced the odds of going to bed without eating food or sleeping hungry. Non-farm income and value of assets for WVZ beneficiaries increased by about 20% and by 22% among treated female-headed households. The results show that diversification and providing grass root training of smallholder farmers increases their resilience to climate shocks.